THE IMPACT OF COVID -19 PANDEMIC ON THE ECONOMIC GROWTH IN BANGLADESH: A CONCEPTUAL REVIEW - Alam, Md. Shahbub; Ali, Md. Jafor; Bhuiyan, Abul Bashar; Solaiman, Mohammad; Rahman, Mohammad Abdur (American Economic & Social Review, 2020)
Since the outburst of Covid-19 in China, the world economy is passing in a turmoil situation. Undeniably the economy of Bangladesh is also grappled by the severe public health crisis of the Covid-19. As the public health emergency is heavily interconnected with economic affairs, it has impacted each of the pillars of the economy of Bangladesh. The main purpose of this paper is to make evaluations of the potential impact of the COVID-19 pandemic on the economy of Bangladesh. This study is based on an empirical review of the recent study works, reports, working papers of home, and abroad regarding economic crisis. The review findings of the paper revealed that the COVID-19 pandemic have significant impacts on the different indicators of the economy of Bangladesh especially, Readymade Garments Sector, Foreign Remittance, Bank and Financial Institutions, Food and Agricultures, Local Trade, Foreign Trade (Export and Import), GDP (Gross Domestic Product), SDGs (Sustainable Development Goal), Government Revenue and Employment etc. This study suggested that as Covid-19 still surfacing all over the world so some steps should be ensured by the government agencies of Bangladesh to mitigate possible threats for the economy.